ANALISIS TINGKAT KEPUASAN PASIEN RAWAT INAP DI RUANG RAWAT INAP RUMAH SAKIT KOTA PADANG - morika, honesty diana; Sari, Putri Minas; Anggraini, siska sakti; Nofia, Vino Rika; MP, Andika Herlina; Sandra, Rhona; Sari, Indah Komala (E-Jurnal Medika Udayana; Vol 11 No 12 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i12.P09, 2022)
Hospital services are needed by everyone for their health needs. It is hoped that good service quality can grow and influence patient decisions and beliefs to use health services. The purpose of this study was to determine the relationship between the quality of nursing services and the level of patient satisfaction in the inpatient ward of the Padang City Hospital in 2022.The type of research used is descriptive with a cross sectional research design. This research was conducted in the inpatient ward of the Padang City Hospital from November 2021 to April 2022. The population used in this study were all patients in inpatient wards 3 and 4 from August 2021 to November 2021 at the Padang City Hospital, totaling 907 patients with 90 samples with accidental sampling technique. Data was collected by means of a questionnaire. Data was processed and analyzed univariately with frequency distribution and bivariate with chi-square test.The results of the study were 50 people (55.6%) were dissatisfied in the inpatient room of the Padang City Hospital in 2022, at most 46 people (51.1%) felt that nursing services were not good in the Padang City Hospital inpatient room in 2022 and there were the relationship between nursing services and the level of patient satisfaction in the inpatient ward of the Padang City Hospital in 2022 (p = 0.036). The conclusion that there is a relationship between nursing services and the level of patient satisfaction in the inpatient ward of the Padang City Hospital in 2022, it is hoped that this research can improve the quality of nursing services such as nurses need to improve their ability to resolve patient complaints and nurses can take the time to listen to patient complaints so that people who hospitalized are satisfied with hospital nursing services.    Keywords :   Patient Satisfication Level,  Nursing Service, City Hospital